Adjustable external horizontal shading slats for daylighting in office buildings in Thailand - Ingabo, Simeon N.; Chaiwiwatworakul, Pipat; Chirarattananon, Surapong (Asia-Pacific Journal of Science and Technology, 2022)
Heat reflective glass is still preferred by designers of commercial buildings in Thailand to reduce solar gain from windows. This hinders the utilization of abundant natural daylight. Shading slats can block beam radiation and also allow for illumination of interior workspaces by diffuse daylight. This study examines the effective operation and performance of adjustable external horizontal slats installed on south-facing windows in office buildings. Experiments were performed in a full-scale room and the results were used to validate a calculation program for simulation. Three slat adjustment schemes were investigated and compared in terms of indoor daylight characteristics, thermal load, annual energy consumption, and energy savings relative to the common case of unshaded windows with heat reflective glass for typical office working hours. Simulations were performed for rooms of varying dimensions and configurations to establish the energy consumption behaviors for workspaces of different sizes. The study established appropriate monthly slat adjustment angles and determined that the installation of adjustable external horizontal shading slats in office buildings could save up to 60% of total lighting and air-conditioning energy consumption compared to workspaces with unshaded heat reflective glass windows.